2020
DOI: 10.3390/ijerph17217801
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acupuncture Treatment with Mortality of Type 2 Diabetes in China: Evidence of a Real-World Study

Abstract: The prevalence and mortality rates of diabetes are increasing globally, posing severe challenges to health systems. Acupuncture is used worldwide as a non-drug treatment for diabetes. However, empirical evidence of the effect of combined acupuncture and drug treatments on diabetic-associated mortality is limited. This study aimed to examine this association of acupuncture treatment with mortality of type 2 diabetes based on real-world data. A four-year cohort study was conducted in Shanghai between 2015 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…[13] There are several studies have reported the therapeutic effects of acupuncture in treating diabetic stroke; in clinical practice, acupuncture has been identified as an important method with promising results in regulating glycemic levels, decreasing the rate of stroke recurrence, repairing motor function, and improving life quality, with no apparent adverse reactions. [14][15][16] Acupuncture appears to be an attractive alternative to pharmacological intervention as a firstline treatment due to its comparatively fewer and less severe side-effects.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%
“…[13] There are several studies have reported the therapeutic effects of acupuncture in treating diabetic stroke; in clinical practice, acupuncture has been identified as an important method with promising results in regulating glycemic levels, decreasing the rate of stroke recurrence, repairing motor function, and improving life quality, with no apparent adverse reactions. [14][15][16] Acupuncture appears to be an attractive alternative to pharmacological intervention as a firstline treatment due to its comparatively fewer and less severe side-effects.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%
“…However, problems such as serious adverse reactions, limited effects, and high final burden impact the therapeutic Studies have shown acupuncture's significant therapeutic effects in improving the conditions of diabetic stroke by affecting metabolism, repairing endothelial cells, and protecting the internal structure of neurons [6,7]. In clinical practice, acupuncture is commonly used in treating the symptoms relate to T2D and stroke; along with the clinical effects such as regulating glycemic levels, decreasing the rate of stroke recurrence, repairing motor function and improving life quality, acupuncture also presents the advantages of safety, cost-efficiency and convenience [8][9][10].…”
Section: Introductionmentioning
confidence: 99%